RETRACTED: Nanostructured Nickel Nitride with Reduced Graphene Oxide Composite Bifunctional Electrocatalysts for an Efficient Water-Urea Splitting - Feng Wang; Dongsheng Zhao; Linbao Zhang; Liming Fan; Xiutang Zhang; Shengnan Hu (Nanomaterials)
A three-dimensional nickel nitride with reduced graphene oxide composite on nickel foam (s-X, where s represents Ni3N/rGO@NF and the annealing temperature X can be 320, 350, or 380) electrode has been fabricated through a facile method. We demonstrate that s-350 has excellent urea oxidation reaction (UOR) activity, with a demanded potential of 1.342 V to reach 10 mA/cm2 and bears high hydrogen evolution reaction (HER) activity. It provides a low overpotential of 124 mV at 10 mA/cm2, which enables the successful construction of its two-electrode alkaline electrolyzer (s-350||s-350) for water–urea splitting. It merely requires a voltage of 1.518 V to obtain 100 mA/cm2 and is 0.145 V lower than that of pure water splitting. This noble metal-free bifunctional electrode is regarded as an inexpensive and effective water–urea electrolysis assisted hydrogen production technology, which is commercially viable.